(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Entrepreneurship is an essential element aiming to be part of this competitive world based on fostering economic growth, creativity, and innovation. The competency-based approach refers to mastering skills and abilities as per the internal will power instead of the external environment’s pace. The present review dealt with studies that focused on entrepreneurship education, competence-based entrepreneurship learning, and a model curriculum. The program should identify and assess trainees’ acquired competencies and develop a communication competency at the entrepreneurship training program’s initial phase. Additionally, the entrepreneurship training programs’ curriculum should develop the trainees’ skills and capabilities. It should also focus on the industry-specific areas leading to economic growth. Hence there is a need to create quality courses by forming a committee of experts from various industries. It concluded that entrepreneurship training programs should develop specific competencies that enable the start-up founders to run their business successfully. Finally, the research considered enhancing motivation and attributes among trainees’ entrepreneurial behaviour and increasing their satisfaction level.